1978
DOI: 10.1063/1.436730
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide chemiexcitation occurring in the reaction between metastable nitrogen atoms and oxygen molecules

Abstract: The infrared emission spectrum of the NO Δv=1 bands, chemiexcited in the reaction between metastable atomic nitrogen and molecular oxygen, has been studied at temperatures of 90–180 K and pressures near 5×10−6 atm. It is concluded that the observed radiation corresponds to an NO vibrational distribution created solely by the chemical reaction, unaffected by any relaxation process(es). Relative rate constants for production of NO into individual vibrational levels are found to be very nearly constant for levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Similar estimations were obtained in Green et al (1984). Rawlins et al (1989) have used the technique which has been employed in Kennealy et al (1978). The principal dierence between their investigation and an earlier study is the more detailed analysis of the contribution of N 2 P O 2 reaction in the observed NOv distribution.…”
Section: Nov Nosupporting
confidence: 52%
See 4 more Smart Citations
“…Similar estimations were obtained in Green et al (1984). Rawlins et al (1989) have used the technique which has been employed in Kennealy et al (1978). The principal dierence between their investigation and an earlier study is the more detailed analysis of the contribution of N 2 P O 2 reaction in the observed NOv distribution.…”
Section: Nov Nosupporting
confidence: 52%
“…9 and 10 in Rawlins et al, 1989). The ®nal conclusions of Rawlins et al (1989) are in signi®cant disaccord with the results of Kennealy et al (1978), and Green et al (1984) showing much higher vibrational excitation of NO on levels v 1±3.…”
Section: Nov Nosupporting
confidence: 45%
See 3 more Smart Citations